Use of Tik Tok for autonomous learning in students of a Private University in Ica – 2023 - Romani Pillpe, Guillermo (2023)
The objective of the study was to determine the use of Tik Tok and its effect for the achievement of autonomous learning in students of a private university in Ica - 2023. The methodology used was Approach: quantitative, Design: pre-experimental, Type: Applied and Level : experimental. The population consisted of N=70 participants, and applied the occasionally simple demonstrated, developed with 52 students corresponding to three specialties. The normality test made it possible to identify that it does not follow a normal distribution, proceeding to contrast the general hypothesis with the Wilcoxon T statistical test. The instruments and technique used were the questionnaire and the observation, respectively. The results obtained indicated that the x̄ analysis statistically presents better results in the posttest 44.00 in relation to the pretest 30.50. In conclusion, it is up to teachers to apply the active Tik Tok methodology to evaluate the advantages and disadvantages to generate autonomous learning.